A Methodology for Affordability Maturity Assessment. Issue 4 (29th August 2016) - Dong, Long; Stracener, Jerrell
Abstract: Systems are becoming more complex while engineering of these systems is facing challenges in cost reduction and shortened schedules due to the fact that technologies emerge and quickly became obsolete. "Do more for less" is a new reality for the U.S. defense industry. As a result, large defense corporations have shifted their cost control effort from business to project management and systems engineering organizations. The realization of affordability in major weapon systems development programs may not be at a tipping point; however, the biggest customer of these weapon developers, that is, the U.S. Department of Defense (DoD), will drive affordability through contract estimation and performance on a firm fixed contract method. This becomes game changing in the defense contract industry, which will drive affordability from offices and manufacturing floors to supplier warehouses. For every complex system development program, the cost to design such system is estimated or predicted before the systems development and demonstration contract is awarded. The transformation of the estimated cost figure is evolving as systems engineering efforts taking place throughout the design life cycle. Thus, without understanding the cost figures during this time, the evolution of cost overrun is inevitable. This paper describes a method to assess the affordability maturity level associated with the systems engineering tasks defined by ISO/IEC 15288 and the Defense Acquisition Strategy, DODI 5000.02. The paper focuses on developing a methodology to insert and assess the maturity of systems engineering efforts and the integration of performance and cost measurement from concept definition through systems design and development. The method is called affordability maturity assessment methodology.